Public knowledge of and attitudes toward genetics and genetic testing in Brunei Darussalam - Jaya, Hazreana; Idayu Matusin, Siti Nur; Mustapa, Aklimah; Abdullah, Muhammad Syafiq; Haji Abdul Hamid, Mas Rina Wati (Frontiers in Genetics, 2023)
The world has been experiencing encouraging research in genetics but current public knowledge, awareness, and perception of this area remains unknown for Brunei Darussalam. This study aimed to investigate the Brunei population’s genetics and genetic testing literacy, and their attitude towards them. A cross-sectional study was carried out targeting public population in Brunei Darussalam. Questionnaires on knowledge and attitudes were randomly distributed in frequented venues in the Brunei-Muara district, and uploaded online for distribution through social media. Responses were scored and analyzed using appropriate statistical methods. Overall, sample population (n = 474) comprised 75.7% female, 64.3% 18-29 years old, 39.7% with a Bachelor Degree education, 2.3% and 5.3% with a personal history and family history of genetic disease(s), respectively. Younger participants scored higher for disease-related questions, showed more concern on the impact of testing on employment, but were more fearful of testing. Higher educational qualifications were associated with a higher knowledge score, a more optimistic view on DNA research, and less reluctance to take a genetic test for an untreatable disease. Participants with a personal history of genetic disease(s) were more knowledgeable and displayed higher curiosity. Participants with a family history of genetic disease(s) were also more knowledgeable and would want testing even for an untreatable disease. Significantly less was known by about the social consequences of testing compared to the medical possibilities. Investigating the knowledge and attitudes of the population is vital preceding efforts towards national adaptation of genetic testing, keeping in mind the various obstacles and issues surrounding the subject.